ANALISIS KEMAMPUAN MENULIS SISWA DALAM SURAT PRIBADI UNTUK SISWA KELAS V SDN 26 PEKANBARU - Khairunnisa Zuhriandini (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2020)
This reaserch examines the ability to write a personal letter of graders V students of SDN 26 Pekanbaru.. This research is a descriptive quantitative research. This research has a population of 97 students. The test used is a story essay test. The tests instruct students to write personal letters on the topics provided and take note of parts of personal letters. The ability of the V graders students of SDN 26 Pekanbaru after being analyzed using categories, from the 6 aspects that have been determined, get the results that on the aspects of the letter date an average of 88.23 with a very good category, the aspects of the mail address category is very good with an average of 96,29, in the aspect of opening greetings the category is very good with an average of 89,00, on the aspect of letter contents an average of 51.22 with enough categories, on the aspect of closing greetings an average of 56.36 with enough categories, in the signature and name sender aspects the category is very good with an average of 88.66. From these results, an overall average of 78.29 was obtained in the very good category.